DAMPAK INTERNET ADDICTION TERHADAP KESEHATAN MENTAL GENERASI Z - Hanifah Arien Faradilla; Ikhrom Ikhrom; Nadya Ariyani Hasanah Nuriyyatiningrum (CV. Adiba Aisha Amira, 2026)
Internet addiction has become a growing concern in the digital era, particularly among Generation Z, who have grown up with technology. This phenomenon is not only occurring in Indonesia, but has also spread across nearly the entire world. Uncontrolled internet use can have serious impacts on adolescents’ mental health. This study aims to explore the effects of internet addiction on four aspects of mental health: self-awareness, self-acceptance, adaptability, and meaning in life. Using a qualitative phenomenological approach, the research involved 20 Generation Z participants selected through purposive sampling. Data were collected through in-depth interviews and screentime documentation, then analyzed using thematic analysis. The results indicate that internet addiction reduces self-awareness, as evidenced by difficulties in recognizing personal emotions and needs, along with impulsive thinking patterns. In terms of self-acceptance, individuals tend to feel pressured and often compare themselves to others on social media, leading to feelings of inferiority. Although some are able to adapt to technological advancements, excessive internet use tends to blur their sense of life purpose. This study highlights the importance of early gadget use regulation by parents and teachers to prevent internet addiction and safeguard the mental health of the younger generation.